Influência do sistema anteoxidante da catalase no ciclo do glioxilato durante o estabelecimento pós-germinativo de cártamo (Carthamus tinctorius L.) e de girassol (Helianthus annuus L.) - Torres, Taffarel Melo (2013)
Oilseeds are a high-value natural resource, due to its use as a substitute for petroleum. However, the storage time can reduce seed viability and oil quality. Therefore, scientific efforts have been made to provide a increment of storage time, germination rates and plant establishment of high-value oilseeds. The seedling establishment depends of the plant pass over the functional transition stage, characterized by a metabolic change from heterotrophic condition to autotrophic one. The storage oil mobilization is performed by β-oxidation process and the glyoxylate cycle. Also, the functional transition involves acclimation to photosynthetic condition, which generally includes the participation of antioxidant system and the reactive oxygen species, the latter are produced in various reactions of primary and secondary metabolism. In the present study, Catalase was inhibited during the functional transition of sunflower and safflower, after were performed many analyzes to elucidate the effects caused on the SOD and APX antioxidant systems. Also, were checked the changes in expression pattern of the glyoxylate cycle enzymes markers, ICL and MLS. It was observed that after CAT inhibition, the SOD and APX antioxidant systems allow the seedling establishment. Besides, was verified that both oilseeds can be accelerate the reverse mobilization and the photosynthetic establishment when Catalase activity has dramatically decreased